Perencanaan Pendidikan Terhadap Perkembangan Sekolah Menengah Kejuruan - Osberth Sinaga; Nurmaulita; Wildansyah Lubis (Paedagogi: Jurnal Kajian Ilmu Pendidikan (e-journal), 2025)
This article aims to analyze educational planning in the development of vocational schools, particularly vocational high schools (SMK). Educational planning is a fundamental aspect of national development, aiming not only to produce academic competencies but also to develop character, creativity, and adaptability in learners. Vocational education at Vocational High Schools (SMK) plays a strategic role in preparing skilled labor aligned with the needs of business and industry. However, challenges in graduate absorption necessitate innovative and adaptive educational planning. Learning models such as Teaching Factory (TeFa), strengthening cooperation with MSMEs, and instilling entrepreneurship are crucial steps. Philosophical foundations, comprehensive planning theories, along with progressive and humanistic educational approaches provide the main framework. Implementation of competency-based curricula, enhancement of qualified educators, industry-standard facilities, project and work-based learning methods, and close collaboration with business and industry are key to successful vocational education and producing graduates ready for work and global competitiveness.